Storage of carbon and water in a periurban area of Tabasco - Domínguez Bautista, Roxana Jhoana; Tobías Baeza, Aydee; Ruíz Acosta, Silvia del Carmen; Salvador Morales, Pedro; Galindo Alcántara, Adalberto; Arrieta Rivera, Agrícola; Sánchez Hernández, Rufo (REVISTA TERRA LATINOAMERICANA, 2019)
As a result of its geographical location and its proximity to the city of Villahermosa in Tabasco, the Ocuilzapotlan-Macultepec road corridor is an area of great potential for urban growth. This has originated intense changes in land use in its peri-urban area that have affected the functions of its natural resources. For this reason, the objective of this research was to analyze land use changes that occurred during the period 2000-2017 and the impact on some environmental functions of the peri-urban areas of said corridor. By means of image analysis we identif ied land uses, land use change rates, and regulation of water flows. Our results suggest that urban areas and grasslands grew by 2.27 and 2.26%, respectively, while forests and wetlands decreased by 11.48 and 1.09%, respectively. Soil carbon concentrations are estimated to be 92.4 ± 5.1, 73.2 ± 2.8 and 220.4 ± 4.6 Mg C ha-1 for meadow, forest and wetland uses, respectively. The shoot compartment of the forest stores 63.27 Mg C ha-1, which, when added to soil carbon, totals 136.47 Mg C ha-1, making this land use the second most important carbon store, only after wetlands. It is concluded that the greatest environmental impact caused by land use change of the peri-urban area of the polygon studied is the reduction of wetlands since they are the main areas of carbon stores and are regulators of water flows.